Long‐Term Distributed Repetitive Transcranial Magnetic Stimulation for Tinnitus: A Feasibility Study. Issue 3 (27th January 2016) - Labar, Douglas; Labar, Amy S.; Edwards, Dylan
Abstract : Objectives: To assess feasibility and tolerability of long‐term distributed therapeutic rTMS for refractory tinnitus, distributed over seven months. Materials and Methods: Eight subjects with refractory tinnitus underwent five weekly sessions of 1800 pulses of 1 Hz rTMS targeted toward the temporoparietal junction. Five weeks later (study week 10), subjects meeting predefined responder criteria entered a monthly rTMS treatment phase, for the next five months. Outcome measures were subject satisfaction and compliance, tinnitus severity daily diaries, standardized tinnitus self‐rating scales, and adverse events. Results: Subject satisfaction was high, and compliance was virtually 100%. The tinnitus handicap inventory and mini‐tinnitus questionnaire scores improved significantly at study week 5 compared with baseline. There were four responders at study week 5; three responders at study week 10; and one responder at study week 30. There were no serious adverse events. Conclusions: Our study demonstrated that rTMS can be delivered in a distributed schedule that is well‐tolerated, feasible and may prove to be clinically beneficial. A long‐term distributed rTMS schedule for tinnitus may warrant investigation as an alternative to the short‐term aggregated treatment schedules more frequently used previously. For the many varied therapeutic uses of rTMS (established and investigational), treatment schedules are relatively unexplored, and deserve further attention.